Acesso a informação sobre assistência segura: educação dos pacientes e acompanhantes - GUTERRES, Ananda Raquel Reis (2019)
become strong and multiply. Objective: ally in the process of caring, risk prevention and the development of a safety culture, which is still incipient in health institutions. Therefore, it is important to have an awareness through education. Objective: To promote access to information for patients and caregivers about preventable risks and safe care. Justification: The health services are complex and have increasingly incorporated technologies and elaborate techniques accompanied by additional risk care. Methods: It is a case study, because is observational descriptive and explanatory, allowing to analyze and describe the development of educational strategy on preventable risk to 25 patients and 28 companions in the period July-August 2016, data collect starting the knowledge gained through the actions with questions and answers about the themes for further analysis. Results: Most of the answers were satisfactory, being in line with the recommendations made during the interventions. Under analysis of the participants' opinion, the actions taken have received good and excellent concepts in most responses. The suggestions and observations of the participants, they considered flaws in the structure of the hospital and in the care provided by professionals, but the actions were praised and the participants recognized their role as minimizing risks in the hospital. Conclusion: The study achieved its goal, however there is a need to support of the institution so that these actions will.